2017
DOI: 10.1021/acs.macromol.7b01941
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Copolymerization and Multicomponent Polymerization of Isobutylene with C4 Olefins

Abstract: Cationic polymerization of isobutylene (IB) in the presence of other C4 olefins, 1-butene (B1), cis-2-butene (C2B), and 1,3-butadiene (BD) using the ethylaluminum dichloride (EADC)·bis­(2-chloroethyl) ether (CEE) complex in conjunction with tert-butyl chloride (t-BuCl) as initiator in hexanes at 0 °C has been investigated. The reactivity ratio of IB r IB = 1100 was determined for copolymerization of IB and B1 at low conversions, using product compositions obtained from inverse gated 13C NMR analysis. The react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 52 publications
1
34
0
Order By: Relevance
“…Results for the polymerization of a C4 olefin mixture at simulated CSTR monomer concentrations corresponding to 70–95% CSTR conversion in hexanes using EADC·CEE ([CEE]:[EADC] = 1.5) are tabulated in Tables S1–S4, and their comparative first-order plots are shown in Figure S2a. The first-order plots move downward with decreasing [IB] similar to the trend observed for polymerization in a batch reactor . Moreover, each first-order plot curves downward with increasing polymerization time due to formation of stable PIB sec -alkoxonium ions via end-capping .…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…Results for the polymerization of a C4 olefin mixture at simulated CSTR monomer concentrations corresponding to 70–95% CSTR conversion in hexanes using EADC·CEE ([CEE]:[EADC] = 1.5) are tabulated in Tables S1–S4, and their comparative first-order plots are shown in Figure S2a. The first-order plots move downward with decreasing [IB] similar to the trend observed for polymerization in a batch reactor . Moreover, each first-order plot curves downward with increasing polymerization time due to formation of stable PIB sec -alkoxonium ions via end-capping .…”
Section: Resultssupporting
confidence: 68%
“…Catalytic chain transfer polymerization (CCTP) in nonpolar solvents at moderate temperatures has developed into one of the most adaptable polymerization techniques for the synthesis of highly reactive polyisobutylene (HRPIB) in recent years. Low molecular weight HRPIB ( M n = 500–5000 g/mol) is a valuable precursor in the preparation of motor oil and fuel auxiliaries. Initially, metal halide (AlCl 3 , GaCl 3 , FeCl 3 , etc.) ether complexes (MX n ·ether) were shown to be better catalysts for the synthesis of HRPIB at moderate temperatures compared to traditional catalysts. However, their application in nonpolar solvents is limited because of poor solubility, which affects the polymerization rate. This issue was lately overcome by employing alkylaluminum dichloride ether complexes as hydrocarbon soluble catalysts. We have shown that the ethylaluminum dichloride (EADC)·bis­(2-chloroethyl) ether (CEE) complex is an effective catalyst, which not only polymerizes pure IB feed but also polymerizes mixed C4 olefin feeds at 0–10 °C to yield up to 88% exo-olefin content . In these studies, polymerization conditions and products have been optimized for a batch reactor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[38] It should be also noted that t BuCl/EtAlCl 2 ÂCEE initiating system, similarly to H 2 O/ i BuAlCl 2 /O i Pr 2 system, [33] could be used for the synthesis of HR PIB from C 4 mixed olefin feed. [39] In addition, this initiating system also displayed improved efficiency toward synthesis of HR PIB under micromixing conditions. [40] In summary, t BuCl/EtAlCl 2 ÂCEE and H 2 O/ RAlCl 2 ÂO i Pr 2 initiating systems allowed to synthesize HR PIB with high exo-olefin content in non-polar reaction media.…”
Section: H 2 O/ralcl 2 / I Pr 2 O Initiating Systemmentioning
confidence: 98%
“…Isobutene is regarded as a monomer for cationic polymerization and for cationic copolymerization with styrene and dienes. The coordination polymerization of such 1,1-disubstituted olefins is rare because of the steric hindrance between the polymer end and the new monomer. Very recently, neutral palladium complexes with phosphine–sulfonate ligand systems have been reported to copolymerize ethylene and 1,1-disubstituted olefins having functional groups.…”
Section: Introductionmentioning
confidence: 99%